Location tracking using UWB-RFID tags - Du, Ruo Gu. (2010)
Ultra-wideband (UWB) is a radio technology that temporally exploits a large portion of the radio spectrum to transmit signals. UWB is robust against fading effect which allows UWB to perform high-accuracy positioning. Nowadays, UWB have drawn increasing interests from industry and academia. Various applications such as location system, real time tracking system, inventory control, search and rescue, home security system are developed. In this project, location estimation theories and principles are reviewed to elaborate the fundation of the project. The details regarding to the system setup are introduced as well. Positioning algorithm and optimization technique are introduced and applied to both single location estimation and movement estimation. The performances are evaluated to demostrate the accuracy of the system. Last but not least, simulation result of a three-dimensional location tracking system is presented to show the possible implementation of three-dimensional location tracking system. The project shows encouraging results for UWB location tracking. It is evident that high accuracy of UWB provides another alternative for location positioning and movement estimation.